Determinants of Farmers’ Income in Rural Agricultural Communities - Luis Enrique Apaut; I Komang Arthana; Maria Indriyani Hewe Tiwu (Research in Accounting Journal (RAJ), 2026)
This study aims to analyze the effect of access to capital, technology utilization, village institutions, and infrastructure availability on farmers’ income in Nitneo Village. This research employs a quantitative approach using multiple linear regression analysis supported by partial and simultaneous hypothesis testing as well as the coefficient of determination. The findings indicate that all independent variables simultaneously have a significant influence on farmers’ income. Partially, technology utilization, village institutions, and infrastructure show a significant effect, while access to capital does not have a significant impact. Furthermore, the model demonstrates a relatively strong ability to explain variations in farmers’ income. Improvements that need to be undertaken include enhancing technology utilization, strengthening village institutions, and improving agricultural infrastructure to sustainably increase farmers’ income.